2012
DOI: 10.1177/1358863x11434197
|View full text |Cite
|
Sign up to set email alerts
|

Significance of high-normal serum uric acid level as a risk factor for arterial stiffness in healthy Korean men

Abstract: A high serum uric acid (SUA) level is a known risk factor for cardiovascular disease. However, little is known about the relationship between arterial stiffness and uric acid in healthy subjects with a normal SUA level. We assessed whether a high-normal uric acid level increased arterial stiffness by measuring brachial-ankle pulse wave velocity (ba-PWV) in healthy subjects. Among 779 subjects who visited the health promotion center, 393 men and 234 women with normal SUA levels (male: 3.5-8.0 mg/dl, female: 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 33 publications
8
26
0
Order By: Relevance
“…Arterial stiffness can be measured at different arterial segments and sites, and by use of different techniques which include regional carotid-femoral pulse wave velocity (cfPWV), brachialankle PWV (baPWV), and local carotid and femoral stiffness. Several studies have assessed the association between uric acid and regional arterial stiffness, with conflicting results [11][12][13][14][15][16][17][18][19][20][21]. However, in most of these studies [12,14,[16][17][18][19][20], arterial stiffness was determined via the assessment of baPWV.…”
Section: Introductionmentioning
confidence: 98%
“…Arterial stiffness can be measured at different arterial segments and sites, and by use of different techniques which include regional carotid-femoral pulse wave velocity (cfPWV), brachialankle PWV (baPWV), and local carotid and femoral stiffness. Several studies have assessed the association between uric acid and regional arterial stiffness, with conflicting results [11][12][13][14][15][16][17][18][19][20][21]. However, in most of these studies [12,14,[16][17][18][19][20], arterial stiffness was determined via the assessment of baPWV.…”
Section: Introductionmentioning
confidence: 98%
“…In a study, arterial stiffness was increased in healthy Korean men (Shin et al, 2012). In the present study, hyperuricemia was defined as the highest quartile of vales (≥6.9 mg/dL in men and 4.8 mg/dL in women).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, hyperuricemia was defined as the highest quartile of vales (≥6.9 mg/dL in men and 4.8 mg/dL in women). Several other studies also used the quartiles of serum uric acid (Lim et al, 2010;Fang et al, 2014;Shin et al, 2012;Ishizaka et al, 2007;Fang et al, 2000). A Japanese study reported that serum uric acid is associated with baPWV, and thus increased arterial stiffness (Ishizaka et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a recent study in subjects with SUA levels within the reference range, those with high-normal SUA levels had an increased AS (higher brachial-ankle PWV) after adjusting for confounding factors [51]. Thus, even SUA levels within the normal range appear to represent a risk factor for AS [51].…”
Section: As In Mets-associated Hyperuricaemiamentioning
confidence: 99%